THE (UN)HEALTHY POOR: WEALTH, POVERTY, MEDICINE AND HEALTH CARE IN THE GRECO-ROMAN WORLD. - Bonati, I. (Akroterion, 2019)
This article explores the connection between the theme of wealth/poverty and medicine in Greco-Roman Antiquity. Special attention is devoted to the changes implied by the transition towards Christianity. The Church has played a fundamental role in the creation of an organized system to assist the sick and needy through the establishment of 'hospitals'. The socio-cultural impact of this topic promotes an interdisciplinary approach based on literary, papyrological and archaeological evidence. In particular, Greek papyri from Egypt provide original information on structures for medical care, philanthropic programs and charitable institutions in the cities and villages of the Egyptian chora.